Dielectric BN nanosheet / PVDF composites with high thermal conductivity. Issue 1 (April 2021) - Zhou, Zhengrong; Zhang, Chi; Zhao, Yalin; Wu, Zhixiong; Zhang, Hua; Guo, Shibin; Huang, Rongjin; Li, Laifeng
Abstract: With the development of electronic devices, high thermal conductivity polymer will become an ideal electronic packaging material. Therefore, Polyvinylidene fluoride (PVDF) nanocomposite was prepared doped with boron nitride nanosheet (BNNS), which has significantly improved thermal conductivity, excellent electrical insulation and outstanding flexibility. These nanocomposite films were prepared by mixing BNNS/PVDF in organic solution, drying, slicing, and then hot-pressing. Compared with the pristine polymers, the nanocomposite films have excellent thermal conduction, which indicates that new high-performance thermal conductivity materials will play an important role in high-power density electronic devices.